Estudo retrospectivo de reabilitação em maxilas atróficas usando fixações zigomáticas - Lima, Humberto Erig (2007)
The application of zygomatic fixations and conventional implants in a immediate loading system for rehabilitation in atrophic upper jaws consists on a recent alternative and it s being widely described on scientific literature, as well as the constant search of success indexes optimization on implants. On this work, it will be aimed to verify the index of permanence of these fixations, characterize the systems, besides verifying the comportment of ZFs in immediate loading procedures, making a long term retrospective study, using a more representative sample. For this study, 59 prompts of patients submitted to upper jaw rehabilitations were evaluated, through the installation of zygomatic and conventional fixations. They were attended on the period of January, 2000 to December, 2006. The data were registered through a chart, specially made for this study, quantified and correlated. It could be verified the application of 151 ZFs and 187 installed conventional implants, being 57, 63% of cases as protocol of two ZFs, associated to four conventional implants in immediate loading system. The index of success was 95, 36% to the ZFs and 99, 47% to the conventional implants submitted to immediate loading or in two surgical